(untitled) (The Pakistan Development Review, 2004)
This paper examines the elasticity and buoyancy of the tax system for the period 1974-75–2003-04. The elasticity of the total tax revenue both with respect to the total GDP and the non-agricultural GDP base is less than unity. Overall, sales tax takes the lead by way of improving revenues. The high coefficient of income tax inclusive of withholding tax, which is an indirect tax, is high. Excluding the withholding tax leads to a lower coefficient. Sales tax with respect to imports and manufacturing also takes care of loss of revenue due to lowering of tariff and excise duties. However, the sales tax coefficient with respect to the GDP base reflects the inclusion of service sector and utilities in the sales tax net, which has serious implications for the poor. The estimates of buoyancy suggest that tax changes did not lead to significant revenue augmentation. The low buoyancy of income tax exclusive of the withholding taxes implies that imposition of massive withholding taxes coupled with an increase in the taxable income limits is working at cross purposes.